2018
DOI: 10.12688/f1000research.13368.1
|View full text |Cite
|
Sign up to set email alerts
|

Absence of the CHEK2 c.1100delC mutation in familial breast and ovarian cancer in Colombia: a case-control study

Abstract: Background: BRCA1 and BRCA2 have been identified as high-penetrance breast cancer predisposition genes, but they only account for a small fraction of the inherited component of breast cancer. To explain the remaining cases, a polygenic model with a large number of low- to moderate-penetrance genes have been proposed; one of these, is the CHEK2 gene (Checkpoint Kinase 2). The objective of this study was to determine the role of the CHEK2 gene, specifically the c.1100delC mutation in familial breast cancer susce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…The CHEK2 c.1100delC truncating mutation, which increases the risk of breast cancer twofold, was widely analyzed. This mutation has a frequency of 0.3–1.2% in European populations [ 135 ] and case-only studies in Brazil, and case–control studies in Colombia and Chile concluded that this variant is almost absent in these populations [ 119 , 123 , 136 , 137 ]. AKT1 is frequently mutated in mammary tumors [ 138 ].…”
Section: Breast Cancer Candidate Gene Studies In Latin Americamentioning
confidence: 99%
“…The CHEK2 c.1100delC truncating mutation, which increases the risk of breast cancer twofold, was widely analyzed. This mutation has a frequency of 0.3–1.2% in European populations [ 135 ] and case-only studies in Brazil, and case–control studies in Colombia and Chile concluded that this variant is almost absent in these populations [ 119 , 123 , 136 , 137 ]. AKT1 is frequently mutated in mammary tumors [ 138 ].…”
Section: Breast Cancer Candidate Gene Studies In Latin Americamentioning
confidence: 99%